IMPLEMENTATION OF AAPM TG-218 FOR PATIENT SPECIFIC QUALITY ASSURANCE (PSQA) IN THE CASE OF THORACIC TARGET REGION USING IMRT RADIOTHERAPY TECHNIQUE WITH EPID aSi-1200 - Listiono, Firza Indrastata; Noor, Johan Andoyo Effendi; Herwiningsih, Sri; Dwiyono, Agustinus Gatot; Martono, Sri; Nugroho, Rafiq Sulistyo; Petrarizky, Alfred Julius (Universitas Mataram, 2025)
The implementation of Patient-Specific Quality Assurance (PSQA) is crucial for ensuring the accuracy and safety of Intensity-Modulated Radiation Therapy (IMRT). This study evaluates the application of AAPM TG-218 recommendations in PSQA for thoracic region treatment using the IMRT technique. The study compares two PSQA methods, Perpendicular Composite (PC) and Perpendicular Field-by-Field (PFF), using Electronic Portal Imaging Device (EPID). Measurements were conducted on 10 IMRT patients using a Varian TrueBeam Linac and Eclipse TPS. The Gamma Index (GI) analysis with criteria 3%/3 mm, 3%/2 mm, and 2%/2 mm was used to assess dose distribution accuracy. The results indicate that the average Gamma Passing Rate (GPR) for 3%/2 mm criteria exceeded 95%, which is appropriate with AAPM TG-218 standards. However, stricter criteria (2%/2 mm) did not reach the minimum recommended values. The study suggests that PSQA using EPID with the PFF method under rotational gantry conditions is the most suitable approach for thoracic IMRT treatment verification. The local standardization recommendations from the results of this study can be used as a reference for determining methodological standards in cases of the thoracic region in the IMRT technique to increase efficiency in clinical applications with similar PSQA dosimetry.